Structural coalescence underlies the aggregation propensity of a β-barrel protein motif - Angelani, Carla Romina (2017)
A clear understanding of the structural foundations underlying protein aggregation is an elusive goal of central biomedical importance. A step toward this aim is exemplified by the β- barrel motif represented by the intestinal fatty acid binding protein (IFABP) and two abridged all-β sheet forms (δ98δ and δ78δ). At odds with the established notion that a perturbation of the native fold should necessarily favor a buildup of intermediate forms with an enhanced tendency to aggregate, the intrinsic stability (δG°H2O) of these proteins does not bear a straightforward correlation with their trifluoroethanol (TFE)-induced aggregation propensity. In view of this fact, we found it more insightful to delve into the connection between structure and stability under sub-aggregating conditions (10% TFE). In the absence of the co-solvent, the abridged variants display a common native-like region decorated with a disordered Cterminal stretch. Upon TFE addition, an increase in secondary structure content is observed, assimilating them to the parent protein. In this sense, TFE perturbs a common native like region while exerting a global compaction effect. Importantly, in all cases, fatty acid binding function is preserved. Interestingly, energetic as well as structural diversity in aqueous solution evolves into a common conformational ensemble more akin in stability. These facts reconcile apparent paradoxical findings related to stability and rates of aggregation. This scenario likely mimics the accrual of aggregation-prone species in the population, an early critical event for the development of fibrillation.